MODERN APPROACHES TO PSYCHOLOGICAL-PEDAGOGICAL DEVELOPMENT OF CHILDREN WITH AUTISM SYNDROME AND THEIR SOCIAL ADAPTATION (Universal International Scientific Journal, 2026)
The causes, classification, and levels of autism syndrome are analyzed, as well as the psychological and pedagogical features of educating children with this syndrome. The main symptoms and problems characteristic of autism, as well as modern approaches to the social adaptation of children, are highlighted.
Keywords: autism, schizophrenia, diagnosis, mental retardation, cognitive reactions, autism symptoms, social adaptation, "early childhood autism"